A biophysical model of how α–tubulin carboxy–terminal tails tune kinesin–1 processivity along microtubule. (7th May 2017) - Sataric, Miljko V.; Sekulic, Dalibor L.; Zdravkovic, Slobodan; Ralevic, Nebojsa M.
Abstract: It appears that so–called post–translational modifications of tubulin heterodimers are mostly focussed at positions of amino acid sequences of carboxy–terminal tails. These changes have very profound effects on microtubule functions especially in connection with cellular traffic in terms of motor proteins. In this study, we elaborated the biophysical model aimed to explain the strategy governing these subtle interplays between structural and functional properties of microtubules. We relied onto Langevin equations including fluctuation–dissipation processes. In that context we found out that small interaction between a charged motor neck domain and oppositely charged carboxy–terminal tail of the α–tubulin plays the decisive role in tuning kinesin–1 motor processivity along microtubules. Graphical abstract: Highlights: Model aims to explain important role of microtubule α–CTTs in regulation of intracellular traffic. Emphasis is given for explaining how the kinesin–1 is tuned by α–CTTs which are post–translationally detyrosinated. Our approach relies on the Langevin equations with inclusion of fluctuation–dissipation processes.